Functional properties of immune cells under the influence of extracts of mushrooms Ganoderma lucidum, Lentinula edodes, Boletus edulis - Duzh Еlena V.; Hancharou Аndrei Y. (Experimental Biology and Biotechnology, 2020)
Тhe water extracts of Basidiomycota division mushrooms such as Boletus edulis, Ganoderma lucidum, Lentinula edodes posessed a wide spectrum of immunomodulatory activity. It was shown that Boletus edulis enhances the expression of surface markers on lymphoid cell lines Jurkat-tat and Daudi, and also increases the expression of reactive oxygen species by dendritic cells, monocytes and peripheral blood neutrophils, activates basophils. There was observed no effect of fungal extracts on NK-cells.